2023
DOI: 10.35848/1347-4065/acbb10
|View full text |Cite
|
Sign up to set email alerts
|

Molecular doping principles in organic electronics: fundamentals and recent progress

Abstract: Molecular doping of organic semiconductors (OSCs) has been widely utilized to modulate the charge transport characteristics and charge carrier concentration of active materials for organic electronics such as organic photovoltaics, organic light-emitting diodes, and organic field-effect transistors. For the application of molecular doping to organic electronics, the fundamentals of molecular doping should be thoroughly understood in terms of doping mechanism, host and dopant materials, doping methodologies, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 101 publications
(136 reference statements)
0
7
0
Order By: Relevance
“…Charge transfer doping refers to the doping process that occurs through charge transfer between a host semiconductor and a molecular dopant (see Figure 2C). 68,69 The molecular dopants act as either donors or acceptors based on their relative energy levels, where donating electrons to the host is energetically favorable when their highest occupied molecular orbital (HOMO) is above the CBM of the MHP (i.e., n‐type doping) and accepting electrons from the host when their lowest unoccupied molecular orbital (LUMO) is below the VBM of the MHP (i.e., p‐type doping), as shown in Figure 2F. In MHPs, various molecular dopants have been employed for molecular doping, such as 2,3,5,6‐tetrafluoro‐7,7,8,8‐tetracyanoquinodimethane (F 4 ‐TCNQ) 70,71 and molybdenum tris‐(1‐(trifluoroacetyl)‐2‐(trifluoromethyl)ethane‐1,2‐dithiolene) (Mo(tfd‐COCF 3 ) 3 ), 72 which are strong molecular acceptors (p‐type dopants), and a strong molecular donor (n‐type dopant) bis(cyclopentadienyl)cobalt(II) (CoCp 2 ) 73 .…”
Section: Electrical Doping In Mhp Thermoelectricsmentioning
confidence: 99%
See 1 more Smart Citation
“…Charge transfer doping refers to the doping process that occurs through charge transfer between a host semiconductor and a molecular dopant (see Figure 2C). 68,69 The molecular dopants act as either donors or acceptors based on their relative energy levels, where donating electrons to the host is energetically favorable when their highest occupied molecular orbital (HOMO) is above the CBM of the MHP (i.e., n‐type doping) and accepting electrons from the host when their lowest unoccupied molecular orbital (LUMO) is below the VBM of the MHP (i.e., p‐type doping), as shown in Figure 2F. In MHPs, various molecular dopants have been employed for molecular doping, such as 2,3,5,6‐tetrafluoro‐7,7,8,8‐tetracyanoquinodimethane (F 4 ‐TCNQ) 70,71 and molybdenum tris‐(1‐(trifluoroacetyl)‐2‐(trifluoromethyl)ethane‐1,2‐dithiolene) (Mo(tfd‐COCF 3 ) 3 ), 72 which are strong molecular acceptors (p‐type dopants), and a strong molecular donor (n‐type dopant) bis(cyclopentadienyl)cobalt(II) (CoCp 2 ) 73 .…”
Section: Electrical Doping In Mhp Thermoelectricsmentioning
confidence: 99%
“…This makes it challenging to achieve effective bulk doping challenging and limits the doping range, unlike conventional doping in inorganic semiconductors. In addition, while their doping mechanisms, such as ion-pair formation or charge transfer complex formation, 68,69 are relatively well understood in organic semiconductors, the mechanisms by which molecular dopants dope MHP host materials have not yet been elucidated. Some studies have reported that molecular dopants can also induce morphological changes in MHPs, 48 highlighting the importance of conducting further studies that can reveal the doping mechanism via a quantitative and systematic assessment of the doping efficiency, and the resulting charge transport mechanism, inclusive of the doping-induced structural changes.…”
Section: Charge Transfer Dopingmentioning
confidence: 99%
“…In addition, their relatively lower thermal conductivity (κ) is also advantageous for a higher TE figure of merit ZT = α 2 σT/κ, which determines the heat-to-electricity conversion efficiency, where α and σ are the Seebeck coefficient and the electrical conductivity, respectively [6]. Thereby, multilateral efforts in material synthesis [7,8], (de)doping methods [9,10], and device physics [11][12][13] have been made in polymer-based TE devices, leading to rapid advances in their performance [14]. Nevertheless, the performance of polymer TE devices in terms of the power factor (PF) α 2 σ is still lower than that of the inorganic materials, which requires further improvement for practical applications in wearable energy harvesters [15] or Internet of Things sensors [16].…”
Section: Introductionmentioning
confidence: 99%
“…Electrical doping of semiconductor layers is a key strategy for improving the performance of electronic devices because doping-related shifts of the Fermi level ( E F ) can increase charge carrier densities in the layers by orders of magnitude. Doped films of conjugated polymers including poly­(3-hexylthiophene) (P3HT) find their applications in organic and perovskite photovoltaic devices and photodetectors as well as in thermoelectrics . Furthermore, P3HT is a well-studied model system to better understand the fundamental processes at work in doping-related charge transfer and the generation of mobile holes in the semiconductor host.…”
Section: Introductionmentioning
confidence: 99%